COMPATIBLE SIMULTANEOUS INTERPENETRATING POLYMER NETWORKS BASED ON EPOXY-RESIN AND POLY(POLY(ETHYLENE GLYCOL)MALEATE) - LIN, MS; JENG, KT; YANG, T (My University, 1993)
Poly(poly(ethylene glycol)maleate) (PPEGMA) was synthesized from poly(ethylene glycol) of molecular weight 200 with maleic anhydride in a molar ratio of 1:1. PPEGMA was then blended with diglycidyl ether of bisphenol A (DGEBA) in various ratios. The formation of hydrogen bonds between PPEGMA and DGEBA was investigated with FTi.r. These blends were then cured with benzoyl peroxide and m-xylenediamine simultaneously to obtain simultaneous interpenetrating polymer networks (SINs). Cure behaviours via exothermic peaks were recorded by dynamic d.s.c. The SINs thus obtained were characterized with rheometric dynamic spectroscopy (r.d.s.) and d.s.c. to check the compatibility of the two constituent networks. Gel fractions were measured with a Soxhlet extractor using acetone as solvent. Hydrogen bonding in the PPEGMA/DGEBA blend was evidenced from the v(C=O) shift to lower wavenumber. During SIN formation, dynamic d.s.c. showed a shift of the exothermic peak to a higher and broader temperature range, indicating a network interlocking effect which was overcome by higher temperature. Full compatibility of PPEGMA/DGEBA SINs was found for all compositions. The compatibility between PPEGMA and DGEBA was supported from the inner shifts of a single damping peak in r.d.s. and a single glass transition in d.s.c. for each of the SINs.
Keywords: SIN; NETWORK INTERLOCK